Geological features for the formation of gas-geochemical fields, including helium and hydrogen, in the water and sediments at the Vietnamese part of the South-China Sea - N. S. Syrbu; Do Huy Kyong; T. S. Yakimov; A. O. Kholmogorov; Yu. A. Telegin; Urumu Tsunogai (Georesursy, 2024)
The paper presents the results of a complex joint Russian-Vietnamese geological, geophysical and oceanographic expedition in the South-China Sea (R/V “Akademik M.A. Lavrentyev”, cruise 88, 2019), as well as related joint RussianVietnamese marine and land researches in the area of north and south Vietnam under a series of local FEB RAS – VAST grants. The organizers of the marine expedition are the V. I. Ilyichev Pacific Oceanological Institute of the Far Eastern Branch of the Russian Academy of Sciences (POI FEB RAS) and the Institute of Marine Geology and Geophysics of the Vietnam Academy of Science and Technology (IMGG VAST). In comparison with the Sea of Japan and the Sea of Okhotsk, it can be noted that the active bottom degassing on the on the Vietnamese shelf and slope have is a local, although the intensity of gas-geochemical anomalies is comparable to similar zones in the Far Eastern Seas. For the first time, anomalous methane fields (up to 5000 nl/l) were found in the water column of the SouthChina Sea, which are comparable to anomalies on the oil and gas shelf and the gas-hydrate-bearing slope of Sakhalin Island.Metamorphosed sedimentary and volcanic rocks were discovered for the first time in the southern part of Catba Island (Gulf of Tonkin), which indicates the introduction of an endogenous body into the sedimentary strata and its further transformation. In connection with the discovery in 2020 of the large Ken Bau gas field at the southern end of the sedimentary basin of the Red River, the forecast of POI scientists about the presence of significant hydrocarbon reserves in this area was confirmed.The work was carried out within the framework of the joint Vietnam-Russia Laboratory for Marine Sciences and Technology (V. I. Ilyichev Pacific Oceanological Institute of the Far Eastern Branch of the Russian Academy of Sciences and the Institute of Marine Geology and Geophysics Vietnam Academy of Science and Technology). The expedition of the R/V “Akademik M.A. Lavrentyev” (cruise 88) is part of a series of expeditions in accordance with the UN Decade dedicated to the Ocean Science for Sustainable Development.